Attitude towards Computers among Primary School Teachers in Kenya: A Case of Siongiroi Divison, Bomet County (International Journal of Engineering and Computer Science, 2018)
In the quest of equipping the pupils with the digital skills required to work in the 21st century knowledge economy, the government of Kenya plans to provide laptops to every primary school class one pupil. If this is to be successful, the question of teacher attitude towards computers is central. This paper presents the results of a survey to study and examine the attitudes of the primary school teachers towards computers. In addition, the study investigated the effects of age, gender, teaching experience, level of education, and computer experience on computer attitude. Data for this study was collected among 114 primary school teachers from Siongiroi Division, Bomet County, Kenya. Measurement tools used was the Computer Attitude Scale (CAS) by Loyd and Gressard (1984). The data acquired was analyzed using descriptive statistics and an analysis of variance (ANOVA).The results indicated that although the teachers have positive attitudes towards computers, they have low confidence level in using the computers. The study also found that the primary school teachers, despite their differences in gender, age, teaching experience and level of education, did not differ significantly (in statistical sense) in their computer attitude. Since teachers portray positive attitudes toward computers, efforts should be geared towards reinforcing the existing positive attitudes. This study highlights the importance of uplifting teachers’ confidence level in using computers